THE ROLE OF PTUN IN ADMINISTRATIVE SUPERVISION OF THE PROTECTION OF CITIZENS' RIGHTS - Sirait, Timbo Mangaranap; Khalimi; Widjaja, Liza (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
In line with developments in science and sociology in society, there are currently many disputes related to state administrative law between state administrative agencies/officials and the community. This article will discuss decisions made by state administrative agencies or officials that are considered to have harmed the interests of the community in legal terms. The research method used is normative jurisprudence through literature study and case study. Primary data was obtained from official copies of decisions from the Supreme Court Decision Directory, while secondary data consisted of relevant administrative law literature and scientific articles. The research questions are: 1) What is the background of the administrative dispute between the State Administrative Body and the Business Entity in the Jakarta Administrative Court Decision No. 425/G/2024/PTUN/Jakarta? 2) What are the implications of this decision for future administrative practices in government (Ius Constituendum)? The findings and conclusions are as follows: First, the background of the administrative dispute in this case is related to an administrative decision (Beschikking) issued by the BKPM, which was deemed detrimental to the legal interests of PT. Global Akses Sinergi, according to the Indonesian legal system, as regulated by the Administrative Court. Second, this decision will contribute to the development of Indonesian administrative law toward the creation of better and more transparent law in the future (Ius Constituendum).